2005
DOI: 10.1007/s11664-005-0270-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ag in the formation of interfacial intermetallic phases in Sn-Zn soldering

Abstract: This study explored the effect of Ag as the substrate or alloying element of solders on the interfacial reaction in Sn-Zn soldering. Results show that instead of Ag-Sn compounds, ζ-AgZn and γ-Ag 5 Zn 8 form at the Sn-Zn/Ag interface. The addition of Ag in Sn-Zn solders leads to the precipitation of ε-AgZn 3 from the liquid solder on preformed interfacial intermetallics. The morphology of this additional AgZn 3 is closely related to the solidification process of Ag-Zn intermetallics and the under intermetallic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 18 publications
5
15
1
Order By: Relevance
“…The additional nodules are AgZn 3 IMCs, as shown in Table 2. This is similar to the result of the study by Song et al [12]. The additional nodules beside the planar layer grow up gradually as the content of Ag increases, as shown in Figs.…”
Section: Microstructure Of Sn-9zn-xag Solderssupporting
confidence: 91%
“…The additional nodules are AgZn 3 IMCs, as shown in Table 2. This is similar to the result of the study by Song et al [12]. The additional nodules beside the planar layer grow up gradually as the content of Ag increases, as shown in Figs.…”
Section: Microstructure Of Sn-9zn-xag Solderssupporting
confidence: 91%
“…A metastable b¢ phase is reported. 18 Since the b¢ phase is formed by quenching, the interfacial reaction product is more likely to be the stable f-AgZn phase, as was illustrated previously. 18 Fig.…”
Section: Resultsmentioning
confidence: 77%
“…Yen et al 17 observed the formation of the three same phases in the Sn-9wt.%Zn/Ag couples reacted at 260°C. Song et al 18 reported the formation of only two phases in the Sn-Zn/Ag couples, and they pointed out that the e-AgZn 3 phase was formed from solidification. Based on the results of different reaction time and quenching rates, it is confirmed that the e-AgZn 3 phase is an interfacial reaction product in the Sn-Zn-Bi/Ag couples.…”
Section: Resultsmentioning
confidence: 99%
“…4a suggests the formation of Ag 5 Zn 8 over the Ag substrate and the subsequent formation of AgZn 3 by the peritectic reaction: L + c-Ag 5 Zn 8 fi e-AgZn 3 . 21 According to Song et al, 22 Ag 5 Zn 8 can easily precipitate over the entire Ag surface due to the similar crystal structure (cubic) and the small lattice mismatch, making it the first IMC to form over a Ag substrate. It should be noted that more than half of the deposited Ag layer remains unreacted.…”
Section: Microstructure Of Sn-1zn/ag Solder Jointmentioning
confidence: 99%